New combinations in the genus Diodella (Rubiaceae, Spermacoceae) - Bacigalupo, N.M. (2006)
Four species of Diodia are transferred to Diodella, and the new combinations are: Diodella gardneri, Diodella mello-barretoi, Diodella sarmentosa and Diodella scandens.